2019
DOI: 10.1002/jqs.3147
|View full text |Cite
|
Sign up to set email alerts
|

How a river submerges into the sea: a geological record of changing a fluvial to a marine paleoenvironment during early Holocene sea level rise

Abstract: Coastal seas, and in particular estuarine systems, were significantly affected by Quaternary sea level changes. Furthermore, the dynamics of shelf and coastal evolution have had a strong impact on coastal landscapes inhabited by humans. The postglacial evolution of the vast North Sea shelf with its huge drainage systems, e.g. the Elbe Paleovalley and its tributary system, is an excellent research target to understand how coastal shelf environments change in response to sea level rise. In this study, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…Numerous studies have identified Late Pleistocene to Holocene channel networks of a similar stratigraphic position to those in this study (Busschers et al, 2007;Fitch et al, 2005;Gaffney et al, 2007Gaffney et al, , 2009Hepp et al, 2017Hepp et al, , 2019Hijma and Cohen, 2011;Prins and Andresen, 2019). During this period, main channels 1 and 2 were active as proglacial channels draining the margin of the Eurasian Ice Sheet into the Late Weichselian North Sea lake, a large proglacial lake proposed to have existed to the south of Dogger Bank (Becker et al, 2018;Hjelstuen et al, 2017;Jansen et al, 1979;Murton and Murton, 2012;Roberts et al, 2018;Sejrup et al, 2016;Toucanne et al, 2010).…”
Section: Where Did the Water Go? Palaeogeography Of The Southern Nortsupporting
confidence: 74%
See 4 more Smart Citations
“…Numerous studies have identified Late Pleistocene to Holocene channel networks of a similar stratigraphic position to those in this study (Busschers et al, 2007;Fitch et al, 2005;Gaffney et al, 2007Gaffney et al, , 2009Hepp et al, 2017Hepp et al, , 2019Hijma and Cohen, 2011;Prins and Andresen, 2019). During this period, main channels 1 and 2 were active as proglacial channels draining the margin of the Eurasian Ice Sheet into the Late Weichselian North Sea lake, a large proglacial lake proposed to have existed to the south of Dogger Bank (Becker et al, 2018;Hjelstuen et al, 2017;Jansen et al, 1979;Murton and Murton, 2012;Roberts et al, 2018;Sejrup et al, 2016;Toucanne et al, 2010).…”
Section: Where Did the Water Go? Palaeogeography Of The Southern Nortsupporting
confidence: 74%
“…CPT L, CPT W; Fig. 3), as marine transgression would have modified the sedimentary environment in the sheltered estuaries to low-energy tidal mudflats, as observed elsewhere in the North Sea during Holocene marine transgression (Coughlan et al, 2018;Gaffney et al, 2009;Hepp et al, 2017Hepp et al, , 2019Prins and Andresen, 2019). The final stage of regional landscape evolution was continued marine transgression, with associated ravinement of the pre-existing topography (Figs.…”
Section: Landscape Evolutionmentioning
confidence: 70%
See 3 more Smart Citations